Healthy lifestyle and its change attenuated the risk of hypertension among rural population: evidence from a prospective cohort study - Ren, Tingyun; Yuchi, Yinghao; Liao, Wei; Kang, Ning; Li, Ruiying; Wang, Chongjian (Frontiers in Public Health, 2025)
ObjectivesLifestyle may potentially influence blood pressure level, but the association of multiple healthy lifestyles with hypertension was limited, especially for rural population. The study aimed to explore the relationship of healthy lifestyles on hypertension, and then whether lifestyle change could influence hypertension in rural adults.MethodsA total of 16,454 participants were enrolled from the Henan Rural Cohort study, in China. The healthy lifestyles score (HLS) was concluded by smoking status, alcohol consumption, physical activity, diet status and body mass index. Associations of HLS and lifestyle change with systolic blood pressure (SBP) and diastolic blood pressure (DBP) were analyzed by generalized linear models, and with hypertension were analyzed by logistic regression model and restricted cubic spline plots.ResultsThe results from the generalized linear models showed SBP and DBP levels decreased with the HLS increasing (Ptrend < 0.01). Compared with participants with lower HLS (scored 0–2), the odds ratios (OR) and 95% confidence intervals (CIs) for hypertension in those with HLS = 3, 4, or 5 were 0.853 (0.737, 0.987), 0.881 (0.754, 1.029), and 0.658 (0.519, 0.834), respectively. And compared with participants with unhealthy lifestyle consistently, those changing lifestyle from unhealthy to healthy had lower levels of blood pressure [β (95% CI): SBP: −1.603 (−2.539, −0.668). DBP: −1.713 (−2.326, −1.100)] and hypertension risk [OR (95%CI): 0.744 (0.594, 0.931)]. Similar results could be found by the sensitivity analysis.ConclusionThe findings showed that healthy lifestyles could reduce blood pressure and hypertension risk, and that implementing healthier lifestyle changes could be an effective strategy to prevent hypertension in rural area.